La autoestima y motivación académica en los estudiantes del 10°año de educación básica de la Unidad Educativa Pompeya de Puyo - Holguin Morales, Brayan Rolando (2023)
ABSTRACT: The present investigation was directed to study self-esteem and academic motivation in the tenth year students of basic education of the Pompeya de Puyo educational unit, debating in a crisis of unsuspected consequences, since what refers to academic motivation occurs when there is low self-esteem. . Methodologically, the research used a quantitative approach, a non-experimental cut design, due to the type it was descriptive and correlational of cross-sectional time. Based on the place of the investigation, it was field and for its data collection the tests were applied : Coopersmith self-esteem inventory and academic motivation scale, to a simple random probabilistic sample of 133 students, in addition to other means such as the IBM SPSS Statistics 25 software for data analysis. Finally, it was concluded that there is a positive relationship between self-esteem and academic motivation in the population studied with a Spearman 's rho statistical value of 0.484 ** and a significant bilateral correlation of 0.00, that is, the higher the self-esteem, the higher the degree of academic motivation.